Factors Related to Smoking Behavior Based on Social Learning Theory in School Students Upper Middle in The District of Bonegunu North Buton District - Anwar, Muhammad; Tasnim, Tasnim; Asri, Andi (Waluya The International Science of Health Journal, 2023)
Background: Data from the North Buton District Health Office in 2021 that Clean and Healthy Life Behavior related to indicators of not smoking in the house is 62.3%. Where out of 10 (ten) health center in the working area of the District Health Office. North Buton Coverage Data for Households who do not smoke in the house, the highest is Kulisusu Health Center at 92.9% and coverage data for Households who do not smoke in the house, the lowest is Bonegunu Health Center at 9.7%. Method: This research uses cross sectional study approach. This research has been carried out for 30 days. The population is 105 people. The research sample is 47 samples behavior smoke teenager class XI and XII. The sampling technique in this study is Simple Random Sampling. Data is processed using test square chi. Results showed that there was a relationship between cognitive X2Count (8.096) and X2Table (3.841), incentive X2Count (10.597) and X2Table (3.841), environment X2Count (20.529) and X2Table (3.841) on smoking behavior of high school students in the District Bonegunu. There is no relationship between Expecta ncy X2Count (0.568) > X2Table (3.841). Conclusion: Research shows that there are connection among cognitive, incentive and environment with behavior smoke whereas hope no there is connection with smoking behavior in high school students, Bonegunu District, North Buton Regency.